THE EFFECT OF FINANCIAL INCLUSION ON HOUSEHOLD POVERTY IN INDONESIA - Vocalyn Khaleda Muliantari; Ilmiawan Auwalin (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Poverty is a major socio-economic problem in Indonesia and is still far from the target set by the government. One of the government's efforts to alleviate poverty is increasing financial inclusion. This study seeks to examine the impact of financial inclusion on household poverty in Indonesia. Financial inclusion is measured through indicators of savings ownership, access to financial services, mobile phone usage, and internet access, and considers demographic variables such as gender of the household head and the location, whether in rural or urban area. This research method used a generalized ordinal logistic regression approach on a sample of 341,802 households in Indonesia obtained from the National Social and Economic Survey (SUSENAS) 2023. The findings show that financial inclusion reduces the likelihood of households falling into poverty or the low expenditure group and increases the chance of households moving to the higher expenditure group. On the other hand, financial inclusion plays a significant role in poverty alleviation and potentially increases household expenditure. Strengthening financial inclusion through financial literacy programs, expanded account ownership, and improve internet access especially among rural households and female-headed households can play a crucial role in reducing poverty in Indonesia.